Covenant Cloaks: Mormon Temple Garments in the Light of Identity Theory - Powell, Adam J. (Material religion, 2016)
It is argued that Mormon temple garments reveal something of the process whereby religious identity receives reinforcement and protection through the stabilizing effects of material symbols. Such symbols are often described as "boundaries" or "boundary markers." In the case of Latter-Day Saints' ritual clothing, however, this essay contends that identity is more often reinforced in relation to the religious community; the garments create cultural meaning and communicate between insiders. This clothing, then, displays many of the hallmarks of the identity theory adumbrated in the mid-twentieth century by sociologist Hans Mol. Mol suggested that identity is the stable half of a stability/adaptability dialectic, and religion is the sacralization of that identity. This paper explores Mormon temple garments as material mechanisms of stabilization, the efficacy of which is to be found in their capacity to anchor emotions, behaviors, and (ultimately) identity in social "covenants." This social cohesion is bolstered by the immutability of the temple garment as an identity generator. Thus, it is argued that Mol's concept of religious identity illuminates at least one attribute of Mormon ritual dress - namely, its identity-conferring potential. Hidden beneath conventional clothing, these garments serve less as boundary markers and more as signifiers of conformity to a social ideal.